2021
DOI: 10.1002/chem.202100523
|View full text |Cite
|
Sign up to set email alerts
|

Acetylenic Replacement of Albicidin's Methacrylamide Residue Circumvents Detrimental E/Z Photoisomerization and Preserves Antibacterial Activity

Abstract: The natural product albicidin is a highly potent inhibitor of bacterial DNA gyrase. Its outstanding activity, particularly against Gram-negative pathogens, qualifies it as a promising lead structure in the search for new antibacterial drugs. However, as we show here, the N-terminal cinnamoyl moiety of albicidin is susceptible to photochemical E/Z isomerization. Moreover, the newly formed Z isomer exhibits significantly reduced antibacterial activity, which hampers the development and biological evaluation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…In summary, we have shown that replacement of the D–E amide bond of albicidin resists protease AlbD cleavage, and at the same time, potency against both G+ve and G–ve bacteria can be increased. Our study on amide bond replacements encourages the application of these isosteres to replace not only other amides of albicidin or related cystobactamide structures but also other peptide structures or aromatic oligoamides. , Whereas the ( Z )-fluoroalkene ( 7 ) is a state-of-the-art well-known isostere, to our knowledge, we report one of the very few examples of an alkyne ( 5 ) considered to act as an amide isostere . This Letter is a further important step in understanding the SARs of albicidin.…”
mentioning
confidence: 73%
See 3 more Smart Citations
“…In summary, we have shown that replacement of the D–E amide bond of albicidin resists protease AlbD cleavage, and at the same time, potency against both G+ve and G–ve bacteria can be increased. Our study on amide bond replacements encourages the application of these isosteres to replace not only other amides of albicidin or related cystobactamide structures but also other peptide structures or aromatic oligoamides. , Whereas the ( Z )-fluoroalkene ( 7 ) is a state-of-the-art well-known isostere, to our knowledge, we report one of the very few examples of an alkyne ( 5 ) considered to act as an amide isostere . This Letter is a further important step in understanding the SARs of albicidin.…”
mentioning
confidence: 73%
“…Both the structure elucidation and the first total synthesis were accomplished by our group . This led to the reporting of a number of albicidin structure–activity relationship (SAR) studies describing building block replacements. , …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The first total synthesis of albicidin established by our group employed an allyl protecting group strategy 23 and paved the way for initial SAR studies. This included many variations of the cinnamoyl residue (building block A) 24,25 and the incorporation of various α-amino acids at building block C. 26,27 A recent study demonstrated the significance and influence of the hydroxy and methoxy substituents on the E and F building blocks on the antibacterial activity. 28 Furthermore, with an azahistidine we have established a new important modification in the central building block C, which resulted in improved antibacterial activities and prevented hydrolysis.…”
Section: Introductionmentioning
confidence: 99%